Association between Chronic Pain and Diabetes/Prediabetes: A Population-Based Cross-Sectional Survey in Saudi Arabia - Khaled K. Aldossari; Mamdouh M. Shubair; Jamaan Al-Zahrani; Abdulrahman A. Alduraywish; Khalid AlAhmary; Salwa Bahkali; Sara M. Aloudah; Sami Almustanyir; Laila Al-Rizqi; Sally A. El-Zahaby; Paivi Toivola; Ashraf El-Metwally (Pain Research and Management)
Background. Diabetes is a debilitating chronic health condition that is associated with certain pain syndromes. The present study sought to evaluate chronic pain and its association with diabetes mellitus at a population level. Methods. A population-based cross-sectional questionnaire survey study was conducted in Al-Kharj, Saudi Arabia, from January 2016 to June 2016. Participants from both private and governmental institutions were selected following a multistage sampling technique and using a cluster sampling method. Anthropometric measurements were taken, including body weight, height, body mass index (BMI) and waist circumference. A blood sample was also drawn from each respondent for fasting blood sugar, HbA1c, and fasting lipid profile. A P value of less than 0.05 indicated statistical significance. Results. A total of 1003 subjects were included for final analysis. Compared to prediabetic and nondiabetic individuals, diabetic subjects had a higher prevalence of lower limb pain (11.1%), back pain (8.9%), abdominal pain (6.7%), and neck pain (4.4%) (X2 = 27.792, P=0.015). In a multiple logistic regression model, after adjusting for age, gender, education level, cholesterol, and smoking status, diabetic/prediabetic patients had a significantly higher prevalence of chronic pain ((OR) = 1.931 (95% CI = 1.536–2.362), P=0.037). Increased age was also significantly associated with chronic pain ((OR) = 1.032 (95% CI = 1.010–1.054, P=0.004). Conclusion. Results of this study found a significant association between diabetes and prediabetes and chronic pain symptoms. Prospective studies are needed to explore temporality of such association.